Indigenous knowledge and conservation status of wild plants collected in Garyaum, North Waziristan, Pakistan - Irfan Ali Shah; Tanvir Burni; Lal Badshah; Noor Ul Uza (Ethnobotany Research and Applications, 2023)
Background: People still use plant-based medicine for their basic healthcare requirements despite having easy access to contemporary medications. Individuals are more dependent on natural remedies, especially in rural areas. In Garyaum, North Waziristan, Pakistan, this study intends to investigate the key native plants utilized in medicine and their applications for treating various illnesses. Objectives: The objectives of this study was to: (1) conduct a systematic examination of the wild plants utilized by the inhabitants of the study area; (2) collect indigenous knowledge concerning wild plants; (3) assess species with considerable cultural importance to the Garyaum inhabitants; and (4) document the conservation status of the collected plants in study area. Methods: Ethnobotanical data based on sociodemographic characteristics were collected using the protocol of (Martin 1995). Techniques included direct led field walks, focus groups, and semi-structured interviews. 95 participants including 81 men and 14 women were interviewed. Quantitative approaches, such as relative frequency citation (RFC), use value (UV), and fidelity level (FL) were also conducted. Results: The participants reported a total of 66 plant species, belonging to 49 genera and 28 families. Of the total reported plants, 47 were fodder species, 35 were medicinal species, 14 were timber species, 20 were fuel species, 11 were fruits species, 7 was vegetable species, 2 were condiment species, 9 were thatching species, 3 were ornamental species while 3 were poisonous in nature. The current findings revealed 45 species (68.18 %) as vulnerable, 9 species (13.63 %) as rare, 8 species (12.12 %) as endangered and 4 species (6.06 %) was found infrequent. None of the species was ranked in the dominant category (IUCN 2001) which clearly described the unpleasant situation of the local flora. Conclusion: It is concluded that local people still rely on plant-based medication for their basic medical requirements. The vast majority of the species are utilized as fuel, wood, and fodder. In addition, plant diversity is diminishing as a result of many anthropogenic influences, infrastructural expansion, and climate change as well. Hence, proper identification and cultivation of significant medicinal and aromatic plants, as well as appropriate conservation and management techniques, are urgently needed in the research region. And the value of floral diversity and conservation must be entrenched in local inhabitants’ children. Keywords: Conservation status, Endangered species, Garyaum, Indigenous knowledge, Quantitative ethnobotany.